Hexapod control through a fractional algorithm - Silva, Manuel F. (2016)
This paper studies the performance of a Fractional Order controller in a hexapod robot with joint leg actuators having saturation. For that objective the robot percribed motion is characterized in terms of several locomotion variables. Moreover, two indices measure the walking performance based on the mean absolute density of energy per travelled distance and on the hip trajectory erros. A set of experiments reveals the influence of the different controller tuning upon the proposed indices and on the feet trajectory tracking.